Eksistensi Lembaga Pendidikan Maktab/Kuttab pada Masa Awal Keislaman: Suatu Kritik Sejarah - Sulfatul Laili (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
The history of existence of kuttab in early Islam is often misunderstood as an educational institution that is systematized with the teaching of the Koran which is taught by Muslims themselves. It is necessary to re-read the history, because there is not enough historical evidence to construct such an understanding. The results of this study indicate that during the early Islamic period the existence of kuttab continued to exist with learning to read, write, basic counting, and poetry, but there was no systematized teaching of reading and writing the Koran as the main activity. In addition, teachers at the kuttab at that time were taught by non-Muslims and prisoners of war, not by Muslims in general. Keywords: kuttab, maktab, history of Islamic education.